Reassessing Signaling Mechanisms in Entrepreneurial Fundraising: A Literature Review on the Role of Communication in Crowdfunding Success - A. Sigit Pramono Hadi; Grace Yulianti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This qualitative literature review explores the signaling mechanisms and communication strategies that influence crowdfunding success in entrepreneurial fundraising. By examining the role of social proof, narrative framing, visual signals, and communication strategies, the review identifies key factors that enhance the effectiveness of crowdfunding campaigns. The findings highlight the importance of creating trust, emotional connections, and sustained engagement with backers through transparent and consistent communication. While signaling mechanisms such as social proof and compelling narratives have been shown to increase credibility, the review also emphasizes potential limitations, including cultural biases and resource constraints. The study contributes to a deeper understanding of how entrepreneurs can leverage communication strategies to maximize crowdfunding success and offers directions for future research on platform-specific and culturally diverse contexts.